Сучасні тенденції підготовки спеціалістів у технічній галузі - Семенець, В. В.; Свид, І. В.; Сайківська, Л. Ф. (ХНУРЕ, 2019)
The report set out the modern tasks of higher educational institutions, raised the issues of the quality of training technical specialists and proposed a method its improving on the example of Kharkov National University of Radio Electronics.
Keywords: вища освіта; технічна освіта; мікропроцесор; мікроконтролер; ПЛІС